The Effect Of Health Education On Knowledge In The Prevention Of Congestive Heart Failure For At-Risk Groups - Rahmania Ambarika; Samrina (Journal of Global Research in Public Health, 2023)
Congestive Heart Failure (CHF) A condition where the heart fails to pump blood to meet the nutrient and oxygen needs of the body's cells. The purpose of this study was to determine the effect of health education on knowledge in the prevention of congestive heart failure for at-risk groups. The research method used is experiment/intervention, pre- experimental design. The population in this study were all participants who were at risk of congestive heart failure in the work area of Upt.Galang District Health Center Tolitoli. The sampling used was purposive sampling so that the sample in this study was based on certain characteristics which were considered to have a relationship with previously known population characteristics. The results showed that after being given health education, p-value = 0,00≥α=0,05 means that there is a significant effect on changes in the level of knowledge after health education is carried out. The conclusion is that there is a significant effect on changes in the level of knowledge after being given health education.